Kompleks Islam Putrajaya (KIP), Putrajaya - Rajuna, Ikhwan Alif; Zailan, Muhammad Izzul Iman; Mohd. Norizan, Nuramylia Syuhada; Zainal Abidin, Zareth Nabila (2024)
This report consists of the interpretation of all activities that we have been learn and observe during the trip to our case study at Kompleks Islam Putrajaya (KIP) located in Precint 3, Putrajaya. This study covers the topic that we have learn throughout the semesters but mainly focusing on the maintenance of this building in terms of the management, operation and financial by the facility management team of TH Universal Builders (THUB). The content of this report is based on the requirements which all information and data are collected to fulfil all the required chapters. Based on the requirement, it must be including the study of detail of property, maintenance management organization, maintenance policy and planning, building design and structural design, building condition assessment, maintenance strategy, legal aspect, financial aspect and the problem and recommendation. The report will be ended with the conclusion on overall study. All the writing on the analysis, explanation and classification are from the point of view of us students of Diploma in Building Surveying. The data presented are from the primary source from the maintenance department, internet and on our observations of the Kompleks Islam Putrajaya. The maintenance management is considered as a vital of every building to ensure the quality of any aspect related to the building will be reserved to the best condition, extend the building life cycle, minimize inconvenience and to provide the comfort, safety and security for the tenants and users. We are hoping for the explanation on the overall contents in this report will satisfy the reader.